The effect of acute beetroot juice consumption prior to climbing on lower-body isokinetic and isometric strength, aerobic power, and muscle soreness among mountain climbers - Alireza Daneshparvar; Mohammad Hemmatinafar; Mohsen Salesi; Rasoul Rezaei; Babak Imanian; Sepideh Pirmohammadi (Journal of the International Society of Sports Nutrition)
Background Beetroot juice (BRJ) contains various bioactive compounds which can enhance athletes” performance. However, there is a limited number of studies assessing the effects of BRJ on climbers” performance and indicators of muscle soreness (MS). Thus, the present study aimed to investigate the effect of consuming beetroot juice acutely before climbing on lower-body isokinetic and isometric strength, aerobic power, and muscle soreness in mountain climbers.Methods In a randomized, placebo-controlled, double-blinded study, 27 climbers (14 males and 13 females) were divided into three groups: Control (CON), Placebo (PLA), and Beetroot Juice (BRJ), with 9 participants in each group. The study evaluated swelling around the thigh (Sw-T), pressure pain threshold (PPT), isokinetic and isometric strength, horizontal jump (HJ), wall-sit, handgrip strength (HGS), flexibility, and the Queen’s College Step test. Testing occurred in three sessions: baseline, climbing, and posttest. At baseline, all participants completed the full battery of tests at Shiraz University. One week later, during the climbing session, they consumed 70 mL of BRJ (400 mg nitrate), PLA, or water 2.5 hours before ascending to 3720 meters. Functional tests (HJ, wall-sit, and estimated VO₂max) were performed at the altitude. After completing these tests, participants immediately descended the mountain. DOMS was assessed using a visual analog scale (VAS) for the quadriceps, hamstrings, and gastrocnemius muscles at the following time points: 2 hours before climbing, and 0 (immediately), 12, 24, 48, and 72 hours after descending. The posttest session, held 72 hours after descending, repeated all baseline assessments.Results The results revealed a statistically significant decrease in DOMS in the gastrocnemius muscles 24 hours post-descending in the BRJ group compared to the control group (p = 0.003, pEta2 = 0.204). However, no changes in DOMS were observed for the quadriceps (p = 0.090, pEta2 = 0.090) and hamstring (p = 0.254, pEta2 = 0.056) muscles. Moreover, notable improvements were observed in PPT (p = 0.001, pEta2 = 0.374), Estimated VO2max (p = 0.016, pEta2 = 0.291), HGS (p = 0.004, pEta2 = 0.270), flexibility (p = 0.003, pEta2 = 0.407), HJ (p = 0.008, pEta2 = 0.155), and isokinetic (peak torque, average power and rate of force development) and isometric (Maximum voluntary isometric contraction) strength indicators in the BRJ groups compare to the other groups (p˂0.05). However, no significant differences were observed in Sw-T between groups (p = 0.305).Conclusions The study suggested that acute consumption of BRJ before climbing improves climbers’ lower-body isokinetic and isometric strength, power, and endurance performance, and it is associated with a reduced perception of muscle soreness.